The impact of risk factors on Vietnamese consumers’ online shopping intentions: a study in Ho Chi Minh City - Phạm, Xuân Kiên; Trần, Quốc Thông; Trần, Thị Xuân Châu; Nguyễn, Thị Mỹ Linh (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2022)
This study aims to explore the factors that influence consumers’ online shopping intentions in Ho Chi Minh City; these factors include financial risk, product risk, safety risk, time risk, social risk, psychological risk and delivery risk. Research is carried out through two main steps: preliminary research (qualitative research) and formal research (quantitative research). Qualitative research was conducted through face-to-face interviews with 5 consumers who have shopped online who are currently living/working in Ho Chi Minh City. Hcm. Quantitative research is conducted through questionnaire interviews. Based on 285 valid samples collected; the reliability assessment results showed that seven scales with 31 observed variables all had Cronbach’s Alpha coefficient greater than 0.7; the discovery factor analysis results showed that 7 factors were extracted with 27 observed variables, and the results of the multiple regression analysis showed that all 7 hypotheses were supported at a meaningful level of 5%. In terms of limited resources and time, this study was not immune to certain limitations, namely using a convenient sampling method and only conducted in the Ho Chi Minh City area. However, with the results achieved, this research can help managers of e-commerce sites better understand the risk factors that affect consumers’ shopping intentions; thereby, e-commerce sites have more effective business strategies and improve competitiveness.